1991
DOI: 10.1152/ajpgi.1991.261.4.g693
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a glutamatergic neural pathway in the myenteric plexus

Abstract: The objective of this study was to determine whether L-glutamate (L-Glu) may serve as a neurotransmitter candidate in the guinea pig myenteric plexus. We observed that [3H]Glu and gamma-[3H]aminobutyric acid were synthesized from [3H]glutamine and released from neurons of the myenteric plexus during K+ and 1,1-dimethyl-4-phenylpiperazinium-evoked depolarization in a concentration-dependent manner. Muscle tension studies performed on ileal longitudinal muscle-myenteric plexus (LM-MP) preparations revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
53
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 0 publications
5
53
0
Order By: Relevance
“…In addition, glutamate depolarizes enteric neurons and mediates fast synaptic transmission in the ENS (Liu et al, 1997). Pharmacological studies have also been consistent with the idea that neurogenic motile (Shannon and Sawyer, 1989;Wiley et al, 1991) or secretory (Rhoads et al, 1995) responses of the gut involve enteric glutamatergic receptors.The abundance of subsets of glutamate receptors that increase [Ca 2ϩ ] i (MacDermott et al, 1986;Hollmann et al, 1991) in the ENS may render enteric neurons vulnerable to glutamatemediated neurotoxicity. The neurotoxic effects of glutamate in the ENS have not been examined; therefore, we determined whether excitotoxicity occurs in guinea pig enteric neurons.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…In addition, glutamate depolarizes enteric neurons and mediates fast synaptic transmission in the ENS (Liu et al, 1997). Pharmacological studies have also been consistent with the idea that neurogenic motile (Shannon and Sawyer, 1989;Wiley et al, 1991) or secretory (Rhoads et al, 1995) responses of the gut involve enteric glutamatergic receptors.The abundance of subsets of glutamate receptors that increase [Ca 2ϩ ] i (MacDermott et al, 1986;Hollmann et al, 1991) in the ENS may render enteric neurons vulnerable to glutamatemediated neurotoxicity. The neurotoxic effects of glutamate in the ENS have not been examined; therefore, we determined whether excitotoxicity occurs in guinea pig enteric neurons.…”
supporting
confidence: 52%
“…In addition, glutamate depolarizes enteric neurons and mediates fast synaptic transmission in the ENS (Liu et al, 1997). Pharmacological studies have also been consistent with the idea that neurogenic motile (Shannon and Sawyer, 1989;Wiley et al, 1991) or secretory (Rhoads et al, 1995) responses of the gut involve enteric glutamatergic receptors.…”
supporting
confidence: 52%
“…Furthermore, electrical activity recorded from the distal ends of cut vagal afferents is modulated by NMDA receptors (42), suggesting that receptors in peripheral vagal afferent membranes may participate in relaying sensory information to the brain. Immunoreactivity for glutamate and vesicular glutamate transporter (VGLUT) has been reported in neurons of enteric plexus of the guinea pig and rat small intestines (45,51). Likewise, immunoreactivity to glutamate has been reported in the intrinsic and extrinsic innervations of the human digestive tract (15), and there is compelling evidence that at least some gastrointestinal vagal afferent terminals are immunoreactive for VGLUTs (32).…”
Section: Discussionmentioning
confidence: 99%
“…Although the activation of nAChRs is the predominant mechanism of excitatory neurotransmission in the ENS, pioneering work initiated by Burnstock in the 1960s (Burnstock et al, 1966;Ambache and Freeman, 1968;Furness et al, 1989;Wiley et al, 1991;Galligan, 1999a, 1999b) demonstrated that autonomic nerves can release many noncholinergic, nonadrenergic neurotransmitters and that multiple mechanisms can contribute to fast synaptic transmission in enteric neurons. Neurons in the ENS can be distinguished on the basis of their electrophysiologic properties into S and AH neurons (Hirst and McKirdy, 1974).…”
Section: Nachrs In the Control Of Gut Functionmentioning
confidence: 99%